Basic Level School Students’ Letter Writing Proficiency - Adhikari, Yam Nath (English Language Teaching Perspectives, 2022)
Letter writing is one of the most important aspect of teaching and learning activities. When the students become competent in letter writing, they can communicate with different firms and institutions. This study proves that the task of letter writing for basic school students in English is a challenging task. The study employed descriptive survey research design. It explores how basic school students perform their level of proficiency in writing letter of apology studying in four schools of Pokhara valley. This study found out that the students of basic school are not instructed well to follow the standard pattern of letters writing during teaching and learning process. The average mark of the sampled schools’ students was 10.48 which showed that the proficiency level of the basic school students’ was not found better. The majority of the students scored below average marks in this study which reveals that both students and teachers need to be trained well to develop the letter writing proficiency of basic school students.